Sintesis Model Inkuiri Terbimbing dan Advance Organizer: Analisis Kekuatan, Keterbatasan, dan Dampaknya Terhadap Kemampuan Pemecahan Masalah Siswa - Gunawan Gunawan; Ahmad Harjono; Mahesti Kusdiastuti; Mir'atun Nisyah (Indonesian Publication Center, 2021)
Inquiry learning fosters physics problem-solving skills but often fails when students lack stable initial knowledge. Conversely, the Advance Organizer (AO) model excels at activating cognitive structures and meaningful learning. This synthesising review analyzes the strengths, limitations, and impacts of integrating guided inquiry with AO on high school students' physics problem-solving abilities based on a comprehensive literature review. The results show that the model's primary strength is providing effective kognitive scaffolding, significantly increasing the